Tracing the Genealogy of Maqāṣid al-Sharī'ah Concept: A Historical Approach - Amir Tajrid (Al-Ahkam, 2021)
This paper aims to explore the emergence, continuity and shifting of the meaning of maqāṣid al-sharī’ah. Initially, maqāṣid al-sharī’ah entered into the study of uṣūl al-fiqh and later became an independent scientific discipline. Historically, the journey of maqāṣid al-sharī’ah has four periods, namely, the pre-codification era, the first development era, the second development era, and the maturation era as a scientific discipline. This paper is qualitative with a descriptive-analytic method, namely exploring the concept of maqāṣid al-sharī’ah in various literature. The findings in this paper are, first, the history of the emergence and development of maqāṣid al-sharī’ah is closely related to the enforcement of Islamic law. Second, the continuity of maqāṣid al-sharī'ah is an ideological concept because it is based on the prevailing paradigm